Examining the Impact of Winter and Spring Soil Temperatures on the Growth of Hypholoma fasciculare, a Potential Biocontrol Agent Against Armillaria ostoyae, in Pine Plantations - Stevens, Ryan; Reyes, Gerardo; Kanavillil, Nandakumar (Frontiers in Forests and Global Change, 2020)
Hypholoma fasciculare is regarded as a potentially effective biocontrol agent against Armillaria root disease. However, trials examining its effectiveness are currently limited to controlled lab conditions and field studies conducted during the summer season. We examined the ability of H. fasciculare to survive and grow underground during the winter and spring seasons to offer insight on its ability to provide year-round protection. Pine blocks inoculated with H. fasciculare were buried in three thinned pine plantations at 30 and 100 cm depths from February 1, 2018 to May 13, 2018 to examine how winter and spring soil temperatures at two different soil depths impacted growth. A significant interactive effect of soil depth and month on soil temperature (F3,40 = 15.94, p < 0.001) was observed. Hypholoma fasciculare continued to grow over the winter and spring seasons (t46 = -3.447, p = 0.001). Mean growth rates were 0.25 ± 0.11 and 0.31 ± 0.10 mm/day at 30 and 100 cm depths, respectively. The growth rate did not vary significantly between the two soil depths tested (t22 = -1.017, p = 0.320). Our study supports developing H. fasciculare as a biocontrol agent against Armillaria root disease given its ability to grow underground during the winter and early spring seasons, a period during which Armillaria has a reduced growing capacity.